2016
DOI: 10.1002/ejoc.201600899
|View full text |Cite
|
Sign up to set email alerts
|

On the Gluco/Manno Paradox: Practical α‐Glucosylations by NIS/TfOH Activation of 4,6‐O‐Tethered Thioglucoside Donors

Abstract: A practical protocol for obtaining α‐glucosides was established. It was found that 4,6‐O‐benzylidene or 4,6‐O‐(di‐tert‐butylsilylene) tethering of glucosyl donors of the thioglycoside type enables highly α‐selective glucosylation under conditions of N‐iodosuccinimide (NIS)/triflic acid (TfOH) activation. The α‐glucosylations were further found to be largely independent of promoter system, temperature, leaving group and anomeric configuration. The results are discussed in the context of the Glucose/Mannose para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…EtOH to give 40β (0.762 g, 1.18 mmol, 94%) as a white solid. 12.0 Hz, J 6b,5 0.8 Hz, 1H, H6b), 4.40−4.34 (m, 1H, H5), 4.24 (dd, J 6a,5 4.9 Hz, 1H, H6a), 3.89 (t, J 3,2/4 9.4 Hz, 1H, H3), 3.80 (dd, 1H, H2), 3.37 (t, 1H, H4), 1.64 (s, 3H, CH 3 ), 1.63 (s, 3H, CH 3 ). 13 Phenyl 2,3,4,6-Tetra-O-benzyl-1-thio-α-D-mannopyranoside (44α).…”
Section: Methyl (6-o-(p-nitro)benzoyl-234tri-o-benzyl-β-d-glucopyrano...mentioning
confidence: 99%
See 1 more Smart Citation
“…EtOH to give 40β (0.762 g, 1.18 mmol, 94%) as a white solid. 12.0 Hz, J 6b,5 0.8 Hz, 1H, H6b), 4.40−4.34 (m, 1H, H5), 4.24 (dd, J 6a,5 4.9 Hz, 1H, H6a), 3.89 (t, J 3,2/4 9.4 Hz, 1H, H3), 3.80 (dd, 1H, H2), 3.37 (t, 1H, H4), 1.64 (s, 3H, CH 3 ), 1.63 (s, 3H, CH 3 ). 13 Phenyl 2,3,4,6-Tetra-O-benzyl-1-thio-α-D-mannopyranoside (44α).…”
Section: Methyl (6-o-(p-nitro)benzoyl-234tri-o-benzyl-β-d-glucopyrano...mentioning
confidence: 99%
“…However, for 1,2- cis linkages as those found in, for example, α-glucosides, α-galactosides, and β-mannosides, other effects and tricks have been used. Among these are the H-bond-mediated glycosylation (Demchenko group), intramolecular aglycon delivery (Hindsgaul, Ogawa, Bols, Stork , and Fairbanks groups), the influence of a 4,6- O -benzylidene direction (β-mannosylation and α-glucosylation mainly the Crich group , but also Bols/Pedersen and Jensen groups), and cyclic sulfonium participation (Boons and Turnbull groups). , …”
Section: Introductionmentioning
confidence: 99%
“…48 Indeed, Crich and co-workers reported that glycosylation of glucosyl donor α-33 predominantly formed the α-linked products. 47b The same observations were made by Heuckendorff and Jensen in 2016, who also reported αglucosylation using 4,6-O-silylene-tethered glycosyl donors, 49 in contrast to the β-selectivity observed for the 4,6-O-silyeneprotected mannosyl donor (Scheme 5). It was rationalized that the difference in stereoselectivity observed for the gluco and manno systems is due to the differing O-2−C-2−C-3−O-3 torsional interactions, as the initially formed covalent triflate collapses to the ion pair, with formation of the solventseparated oxocarbenium ion being less endothermic than that of its mannosyl counterpart.…”
Section: Glycosylations Using Torsionallymentioning
confidence: 99%